Clinical and microbiological effects of different antimicrobials on generalized aggressive periodontitis - Christiana Xajigeorgiou (journal of clinical periodontology, 2006)
Aim: To evaluate and compare the effects of adjunctive metronidazole plus amoxicillin, doxycycline and metronidazole on clinical and microbiological parameters in patients with generalized aggressive periodontitis. Material and Methods: Forty-three patients participated in this randomized clinical trial divided into four groups. Six weeks after scaling and root planning (SRP), groups 1–3 received adjunctive metronidazole, plus amoxicillin, doxycycline and metronidazole respectively, and group 4 acted as controls. Clinical recordings concerning probing depth, probing attachment level and bleeding on probing were performed at baseline, 6 weeks after SRP and 6 months from baseline. Subgingival samples were analysed using the ‘checkerboard’ DNA–DNA hybridization for Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans, Tannerella forsythia and Treponema denticola. Results: All treatments resulted in improvement of clinical parameters (ANOVA p40.05). Systemic administration of metronidazole plus amoxicillin or metronidazole resulted in statistically significant greater reduction of the proportion of sites 4 6mm than SRP (z-test, po0.05). These antimicrobials yielded a significant effect on levels of important periodontal pathogens for 6 months. Conclusion: Adjunctive metronidazole plus amoxicillin or metronidazole alone (when A.actinomycetemcomitans is not involved) is effective in deep pockets of aggressive periodontitis patients.